Make your own ideabook : create handmade art journals and bound keepsakes to store inspiration and memories - Nerjordet, Arne, 1963-; Zachrison, Carlos, 1970- (Trafalgar Square, 2016)
"A keepsake; a treasure trove; a work of art; a source of inspiration; a method of organization; a peek inside the chaos and creativity of our own minds. An ideabook can be any one of these, or all of them, or something else entirely: a collection of memories, a way to store recipes or patterns, a genealogical journal, a planner for a wedding or renovation or garden ... With Arne and Carlo's ... handcrafting genius to guide you, learn how you can make and enjoy your own ideabooks--to celebrate, remember, or reach out for all that lies ahead"--Amazon.com.